2023
DOI: 10.3126/jtha.v5i01.56187
|View full text |Cite
|
Sign up to set email alerts
|

Nexus between Tourism Industry and Economic Growth of Nepal

Bharat Ram Dhungana

Abstract: The tourism sector is essential to economic growth and has the capacity to stimulate the economy. The aim of this paper to assess the relationship between tourism industry and its economic growth. The gross domestic product (GDP) indicates the economic growth and tourism industry development relates to tourist arrivals, length of stay, and gross foreign exchange earnings from tourism. This study is grounded on secondary data collected from the Economic Survey of Nepal and the Nepal Tourism Statistics from 2000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…The tourism industry in Nepal is a vital component of the country's economy. Several research studies find that there is a nexus between the tourism industry and economic growth (Badulescu et al, 2020;Dhungana, 2023;Songling et al, 2019). It has been demonstrated that countries with relatively abundant natural resources will prioritize tourism and have faster rates of economic expansion (Sequeira & Maçãs Nunes, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The tourism industry in Nepal is a vital component of the country's economy. Several research studies find that there is a nexus between the tourism industry and economic growth (Badulescu et al, 2020;Dhungana, 2023;Songling et al, 2019). It has been demonstrated that countries with relatively abundant natural resources will prioritize tourism and have faster rates of economic expansion (Sequeira & Maçãs Nunes, 2008).…”
Section: Introductionmentioning
confidence: 99%